A systematic review of musculoskeletal injuries in professional golfers - Robinson, P.; Murray, I.; Duckworth, A.; Hawkes, R.; Glover, D.; Tilley, N.; Hillman, R.; Oliver, C.; Murray, A. (British Journal of Sports Medicine, 2021)
Background The distribution of professional golfing injuries is poorly understood.